Strategi Kepala Sekolah dalam Mengelola Konflik Internal di SMP NU Bululawang Kabupaten Malang - Anang Ismail (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Conflict in an organization is something that cannot be avoided because it will always exist in every cooperative relationship between individuals, groups and organizations. Conflict is actually something natural which is within a certain time limit can be positive for school development, but it must be managed properly and carefully. If it crosses the line, the conflict can have fatal consequences. The principal as the highest leader in the school must be able to manage the conflict, so that it can provide positive benefits and avoid negative consequences. Likewise at SMP NU Bululawang, the principal is required to be able to manage the conflict well. This study aims to determine the principal's strategy for managing the conflicts that occur at SMP NU Bululawang. The method used in this study is Field Research by using a phenomenological design. The results showed that the principal in managing conflict was carried out through three strategies, namely the strategy of collaboration, accommodation, and compromise. With the three ways of handling conflict in SMP NU Bululawang Malang Regency, it has the ability to reduce or avoid the possibility of a social explosion in the school environment.